Penerapan Algoritma Fisher Yates Shuffle dan Linear Congruent Method Pada Simulasi Ujian Toefl Berbasis Android - Fauji Ahmad (JURIKOM (Jurnal Riset Komputer), 2018)
In facing global competition to enter institutions or companies, most companies or agencies apply various conditions to enter the agency or company, one of which is often used by large companies is to master English to communicate with the outside world. The number of Toefl questions that we can get from the internet or from Playstore like the Toefl simulation has the same sorting if made from the same Vendor. Then an Android-based Toefl simulation was made to randomize the sequence of questions if more than one person playing. For randomization of the sequence of questions, the author applies the Fisher-Yates Shuffle algorithm and Linear Congruent Method which have been proven to be able to randomize the questions well.